2017
DOI: 10.1016/j.bmc.2017.03.061
|View full text |Cite
|
Sign up to set email alerts
|

An integrated chemical biology approach reveals the mechanism of action of HIV replication inhibitors

Abstract: Continuous flow (microfluidic) chemistry was employed to prepare a small focused library of dihydropyrimidinone (DHPM) derivatives. Compounds in this class have been reported to exhibit activity against the human immunodeficiency virus (HIV), but their molecular target had not been identified. We tested the initial set of DHPMs in phenotypic assays providing a hit (1i) that inhibited the replication of the human immunodeficiency virus HIV in cells. Flow chemistry-driven optimization of 1i led to the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 52 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…A set of dihydropyrimidinone (DHPM) derivatives, which probably act as NNRTIs and their activity against K103N/Y181C mutant RT are described [ 71 ]. A set of marine diterpenes (dolabelladienotriol, THD and its derivatives) has been docked with various mutant forms of RT containing mutations: K103N, V106M, Y188L; V106M, P225H; V106A, Y181I; V106A, Y181C, G190S; K103N, Y188L; K103N, Y188L, G190E [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of dihydropyrimidinone (DHPM) derivatives, which probably act as NNRTIs and their activity against K103N/Y181C mutant RT are described [ 71 ]. A set of marine diterpenes (dolabelladienotriol, THD and its derivatives) has been docked with various mutant forms of RT containing mutations: K103N, V106M, Y188L; V106M, P225H; V106A, Y181I; V106A, Y181C, G190S; K103N, Y188L; K103N, Y188L, G190E [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…It may be concluded that the existing application of the molecular docking to HIV-1 RT resistance studies lead mainly to the discovery of new molecules targeted at well-investigated mutant RT forms [ 67 , 68 , 69 , 70 , 71 , 72 ]. But some approaches are directed to research studies of known molecules targeted at comparatively rare RT mutants [ 65 , 66 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The interests of using DHPMs in medicinal chemistry is dramatically growing ( Figure 1 ) due to their therapeutic and pharmacological properties [ 4 , 5 ]. It has been reported that DHPMs can possess various biological activities including antiviral [ 6 , 7 ], antitumor [ 8 ], anti-inflammatory [ 9 ], antidiabetic [ 10 ], antibacterial [ 11 ], antifungal [ 12 ], anti-epileptic [ 13 ], antimalarial [ 14 ], and antileishmanial [ 15 ] and others upon suitable structural modification. The highly functionalized DHPM 10, termed MAL3-101, had been observed with effect of inducing breast cancer cell apoptosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we would like to disclose a novel interrupted Ugi reaction, exploiting for the first time the imidazole ring, as a soft nucleophile able to intramolecularly intercept the nascent nitrilium ion. This intermediate enables the formation of otherwise synthetically challenging substituted imidazopyrazines, in excellent yields and under mild reaction conditions (r.t. in MeOH) Multicomponent reactions represent a powerful chemical tool to expedite medicinal chemistry and early drug discovery programs [29], especially when combined with automation and flow synthesis [30,31,32].…”
Section: Introductionmentioning
confidence: 99%